Two new color （n, n）-secret sharing schemes - YI Feng; WANG Dao-shun; LUO Ping; DAI Yi-qi (Tongxin xuebao)
Two methods of（n,n）-secret sharing scheme for color images were presented.Decryption was processed by XOR operation.The reconstruction complexity of the proposed scheme is equivalent to the visual secret sharing scheme,furthermore the quality of the reconstructed image of the proposed scheme is better than color visual secret sharing scheme.